The Diagnostic Value of Interleukin‐2 and Interferon‐γ Induced by Fusion Protein (ESAT‐6/CFP‐10/Rv1985c) for Active Mycobacterium tuberculosis Infection - Zhao, Zhipeng; Li, Runqing; Zhao, Xiuying; Wang, Yujie; Lin, Minggui; Wei, Qian; Li, Xiaochen; Xiong, Pan (Journal of clinical laboratory analysis, 2025)
ABSTRACT Objective This study aimed to evaluate the diagnostic ability of interleukin 2 (IL‐2) and interferon gamma (IFN‐γ) release assay induced by the fusion protein (ESAT‐6/CFP‐10/Rv1985c) for detecting active tuberculosis (ATB) in clinically visiting patients. Methods A total of 970 subjects (215 in ATB group and 755 in non‐ATB group) underwent both an interferon‐γ release assay (IGRA) and a TB‐DNA PCR assay. Using clinical diagnosis as the gold standard, both qualitative and quantitative test results for IL‐2 and IFN‐γ were analyzed. Subsequently, the diagnostic ability of IL‐2 and IFN‐γ to screen for ATB among the high‐risk population was then evaluated. Results IL‐2 exhibited higher specificity, while IFN‐γ demonstrated higher sensitivity in distinguishing between ATB and non‐ATB subjects. The sensitivity of the serial application of IL‐2 and IFN‐γ had no significant difference (p = 1.000) compared with IFN‐γ; the specificity of the serial application of IL‐2 and IFN‐γ had no significant difference (p = 0.708) compared with IL‐2. Quantitative analysis of the results revealed that the IL‐2 and IFN‐γ values were significantly higher in the ATB group compared with the non‐ATB group. Additionally, the combined predictors of IL‐2 and IFN‐γ did not show a significant difference compared with IL‐2 alone (p = 0.324) or IFN‐γ alone (p = 0.405). Conclusions This study demonstrated that IL‐2 and IFN‐γ release assays induced by the fusion protein (ESAT‐6/CFP‐10/Rv1985c) were valuable for distinguishing ATB from non‐ATB subjects, with IL‐2 exhibiting higher specificity and IFN‐γ demonstrating higher sensitivity. A total of 970 cases, consisting of 215 active tuberculosis (ATB) cases and 755 non‐active tuberculosis (non‐ATB) cases, were enrolled in this study. The results indicated that the release assays of interleukin‐2 (IL‐2) and interferon‐γ (IFN‐γ) induced by the fusion protein (ESAT—6/CFP—10/Rv1985c) were of great value in differentiating ATB from non‐ATB subjects. Specifically, IL‐2 showed higher specificity, while IFN‐γ demonstrated higher sensitivity.